A Note on the Stability of $K$-g-Frames (Communications in Mathematical Research, 2019)
In this paper, we present a new stability theorem on the perturbation of$K$-g-frames by using operator theory methods. The result we obtained improves onecorresponding conclusion of other authors.
Keywords: g-frame; $K$-g-frame; frame operator; stability.